Can At-Risk Youth Be Diverted From Crime?: A Meta-Analysis of Restorative Diversion Programs. (October 2016) - Wong, Jennifer S.; Bouchard, Jessica; Gravel, Jason; Bouchard, Martin; Morselli, Carlo
Existing reviews of the impact of restorative justice programs on juvenile recidivism have reached mixed conclusions. The present meta-analysis identified relevant studies through a systematic search of 20 databases over a 25-year period as well as the ancestry method. Application of inclusion criteria resulted in a set of 21 studies contributing 21 independent effect sizes. Programs were found to be overall effective at reducing recidivism, with a pooled odds ratio of 1.28. Subgroup analyses indicate strong evidence that study and treatment characteristics play a role in evaluation results, such as strength of research design and racial/ethnic mix of program participants. Overall quality of the literature is relatively weak, with the large majority of studies derived from non-peer-reviewed sources and a lack of detail presented on treatment characteristics. Limitations with respect to exclusion criteria, sample sizes, and between-study heterogeneity are discussed.